From Placenta to Polycystic Ovarian Syndrome: The Role of Adipokines. (26th September 2016) - Sartori, Chiara; Lazzeroni, Pietro; Merli, Silvia; Patianna, Viviana Dora; Viaroli, Francesca; Cirillo, Francesca; Amarri, Sergio; Street, Maria Elisabeth
Abstract : Adipokines are cytokines produced mainly by adipose tissue, besides many other tissues such as placenta, ovaries, peripheral-blood mononuclear cells, liver, muscle, kidney, heart, and bone marrow. Adipokines play a significant role in the metabolic syndrome and in cardiovascular diseases, have implications in regulating insulin sensitivity and inflammation, and have significant effects on growth and reproductive function. The objective of this review was to analyze the functions known today of adiponectin, leptin, resistin, and visfatin from placenta throughout childhood and adolescence. It is well known now that their serum concentrations during pregnancy and lactation have long-term effects beyond the fetus and newborn. With regard to puberty, adipokines are involved in the regulation of the relationship between nutritional status and normal physiology or disorders of puberty and altered gonadal function, as, for example, premature pubarche and polycystic ovarian syndrome (PCOS). Cytokines are involved in the maturation of oocytes and in the regular progression of puberty and pregnancy.